HU Common Spaces in Housing Units - Montiel, Rozana (Infonavit, 2018)
https://infonavit.smart-ed.mx/cgi-bin/koha/opac-retrieve-file.pl?id=34ab7de605f8c1db6eadb2376c3e48a4Mejorando la Unidadhttps://infonavit.smart-ed.mx/cgi-bin/koha/opac-retrieve-file.pl?id=34ab7de605f8c1db6eadb2376c3e48a4 (Retrofitting Housing Projects) was a program developed as part of this commitment with the aim of upgrading the living conditions in housing projects at the same time as making interventions in their common or public spaces. This program was designed by the Institute of the National Housing Fund for Workers ( Infonavit) and implemented through its current Research Center for Sustainable Develop ment (CIDS), in conjunction with the Ministry of Agrarian, Territorial and Urban Development (SEDATU), the Federal Mortgage Society (SHF), the National Housing Commission (CONAVI), the Government of Mexico City (CDMX) and local administrations of each City borough.